تطوير مادة المحادثة على أساس المدخل العلمي - سيف المصطفى; موعظة الحسنة سيف (Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2017)
Textbook is one of the most important elements for a successful teaching and learning of Arabic.  Such a textbook serves to convey concepts and knowledge, to develop capacities and skills, and to satisfy needs and interests. Some students felt discouraged to speak in an Arabic speech class due to inconvidence and fear of error. Some found the Arabic speech class boring for its lacks lifely activities. Given the mentioned problems, this research aims at developing a textbook for Arabic speech course, whose materials are derived from real conversations. The developmental research uses ADDIE method, carried out in five stages: needs and problems analysis, product design, product development, product experimentation, and product evaluation. Data are collected through observation, interview and questionnaire, and are analysed using the Likert model. The resulted textbook, entitled “I love Arabic Conversation”, produced on the basis of the scientific approach, has been trialed in the Batu Bilingual High School, showing that it is valid and fits the students’ needs and skills well. Keyword: Arabic, conversation, texbook development, scientific approach.